Public Policies in the açaí production and trade chain: security and food sovereignty in the Amazon and the 2030 agenda (Research, Society and Development, 2022)
The açaí is a fruit that has had an expressive growth in its production and commercialization in the last two decades, which is based on the discoveries of its nutritional and functional properties in the human diet. This study had as its guiding question “How is Food Safety organized in the açaí commercial chain with a view to contributing to objective 2 of the 2030 Agenda? The objective was to carry out an integrative review of the technical and scientific material published, being organized into three chapters: 1. Public Policies in the Açaí Productive and Commercial Chain, 2. Safety and Food Sovereignty in Açaí Consumption in the Amazon and 3. Consumption Açaí and Agenda 2030. The following keywords were used: açaí; food security; Agenda 2030. The results were presented in two summary tables. The publications brought in their content aspects about changes in the way of production and commercialization in order to meet the growing demand, as well as the quality of the product for the national and international market. Another point analyzed was the public policies established in this process. There was a lack of public policies for the cold chain in the management of the fruit, given its perishability, making it a critical point of control regarding the quality of the product for local populations dependent on the costs that this treatment generates. It was concluded that in order to reach objective 2 of the 2030 Agenda, public policies are needed to guarantee the production and consumption of quality açaí for the loco-regional population, the sustainability of this system in guaranteeing the identity and social representation of this food. for this present society and future generations.